Supply Chain Management and Recommendations for Implementation in the Defense Industry: A Literature Review - Yusuf , Andi; Soediantono, Dwi (International Journal of Social and Management Studies, 2022)
Supply Chain Management has been applied in various industries to increase productivity. The purpose of this article is to explore the benefits of implementing Total Productive Maintenance (TPM) in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles published from 2010 to 2021 regarding the implementation of Supply Chain Management in various industrial sectors and the defense industry. The analysis used used 25 content analyzes of journal articles, which had been collected and then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the implementation of the results of the literature review analysis states that the effect of implementing supply chain management contributes to minimizing inventory SCM activities can reduce inventory levels, through intensive control and information. Reducing costs Integration of product flow from suppliers to end consumers can reduce costs. Reducing costs lead time Proper coordination, systems, data and information in the implementation of the flow of goods can reduce lead times for procurement, production and distribution. Increase revenue. Loyal customers and partners with the company can increase company revenues. On time delivery An integrated and controlled goods flow system can resulting in the delivery of goods on time. Ensure the smooth flow of goods The integration of all elements of SCM through information systems, can facilitate the flow of goods. Based on the literature review, supply chain management recommended to be applied to the defense industry. Based on the literature review, Supply Chain Management is recommended to be applied to the defense industry.